Brand Positioning Media Sosial Terhadap 2 Merek Fashion Muslim Digital Branding Pendekatan UU Perlindungan Konsumen - Hapsari, Nia Puspita; Rurianto, Joko; Ruswanti, Endang; Sari Sumitro, Dewi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The development of Muslim Fashion in Indonesia, and abroad shows significant growth, especially in the Muslim Fashion sub sector utilizing social media as the main means of digital branding. This study aims to analyze brand positioning through social media to strengthen brand image, and protect consumer rights based on Law No.8/1999 concerning Consumer Protection. The research method uses a descriptive qualitative approach with case studies on local Muslim Fashion brands such az Zashi, and Buttonscarves. The results show that brand positioning marketing strategies on social media have succeeded in fostering consumer trust through the values of product authenticity, emotional engagement, and information transparency. However, challenges arise in aspects of digital consumer protection such as product authenticity, misuse of personal data, and misleading promotional claims. The implications of the study emphasize that the effectiveness of digital brand positioning must be integrated with compliance with the principles of consumer protection, information transparency, and digital communication ethics to maintain the sustainability of the Muslim Fashion creative industry in the era of the digital economy 5.0.